ISOTOPIC REGIME OF SUBGLACIAL LAKE VOSTOK ON EVIDENCE FROM DEEP ICE CORE STUDIES - A. A. Ekaykin; V. Ya. Lipenkov; A. V. Kozachek (Лëд и снег, 2015)
On the 5th of February 2012 the long-lasting project of deep ice drilling at Russian Antarctic station of Vostok was completed by the penetration to the subglacial lake at the depth of 3769.3 m. The study of the ice core representing the frozen lake water and obtained as a result of the drilling, has allowed to make preliminary conclusions on the lake hydrological regime before its direct studies. In this work we present the new isotopic data (dD and d18O) from the 5G-2 ice core from the depth interval 3600–3720 m. The measurements were performed in the recently established Climate and Environment Research Laboratory of Arctic and Antarctic Research Institute (St. Petersburg,Russia). The comparison of the new isotope profile with the previously published 5G-1 data (3540–3650 m) demonstrates a good reproducibility, which means a satisfying quality of the measurements. The analysis of the whole available lake ice thickness isotope profile (3540–3720 m) has allowed to obtain a new information on theLakeVostok’s hydrological regime. Based on the isotopic behavior, the lake ice core is divided into three sections. The first (3540–3619 m) corresponds to the so-called «lake ice 1», the ice containing visible mineral inclusions that was formed close to the western lake shore. The isotopic variability in this section was formed due to the changing conditions and mechanisms of the ice formation (ice accretion rate, concentrations of the frazil ice crystals and frozen water pockets). The second (3619–3647 m) is characterized by a weak correlation between deuterium and oxygen 18, which is interpreted as an influence of the hydrothermal activity on the lake’s isotopic regime. In the third section (3647–3720 m), formed over the deep basin in the southern part of the lake, the isotopic variability is reduced due to the relatively stable steady-state conditions of the ice formation. At the same time, the signature of the lake water isotopic variability is observed here, which is attributed to the pulsations of the flux and/or isotope content of the melt glacier waters coming from the northern part of the lake. In turn, this means not complete mixing of the lake source waters with the resident water of the lake and, thus, that the water layer just beneath the glacier in the Vostok station area is not representative in terms of the conditions in the main lake body. We suggest that the future direct lake studies must include water sampling at different depths from the lake-water interface to the bottom. Meanwhile, in the nearest future this study will be developed by the completing of the measurements of the whole 5G-2 core (to the depth of3769 m), as well as the analysis of the short-term (1 cm) variations in the bottom part of the ice core, where the isotopic signal must be fully preserved without being erased by the molecular diffusion. Also, the measurement of the first lake water sample recovered from the drill after the penetration will allow the comparison with the lake ice isotope content in order to experimentally define the effective isotope fractionation coefficient and thus constrain the possible mechanism of the lake ice formation.